Mindfulness and Empathy: Mediating Factors and Gender Differences in a Spanish Sample - de la Fuente-Anuncibay, Raquel; González-Barbadillo, Ángela; Ortega-Sánchez, Delfín; Pizarro-Ruiz, Juan Pablo (Frontiers in Psychology, 2020)
Numerous research studies link mindfulness training to improved empathy. However, few studies focus on the mediating factors of empathy. This work has three objectives: (a) to analyze the possible mediation of mindfulness as a feature in this relation, (b) to analyze the mindfulness factors that mediate in the increase of empathy and (c) to analyze gender differences. The sample was composed of 246 Spanish-speaking university students (M= 24.08 years, SD=8.43). The instruments used were the Five Facet Mindfulness Questionnaire (FFMQ) and the Toronto Empathy Questionnaire (TEQ). For data analysis, the indirect effect was calculated using 10.000 bootstrap samples for the bias-corrected bootstrap confidence intervals (BCI). With respect to gender differences the results confirm differences in FFMQ finding higher scores in men who practice mindfulness than women and men who do not. The improvement of empathy is mediated by the changes in cognitions contemplated by the mindfulness construct (B=.075, p<.001), disappearing in the presence of this mediator, the direct effect of mindfulness practice on empathy (B=1.271, p>.05). Observing and describing are the FFMQ factors that mediate significantly between mindfulness practice and empathy.